A historical and comparative study of human rights violations in criminal investigations in Lesotho. - Lenka, Thamae Caswell Liphapang (University of the Free State, 2010)
The issue of human rights violations in criminal investigation emerges as one of the much debated subjects amongst academics since the inception of the idea of the fundamental human rights all over the world. Human rights remain a center pillar and a pivot around which criminal justice system revolves. In Lesotho, for example, the question of human rights has been critical in the light of the fact that, since independence on the 4th of October 1966, there was never a real and tangible instrument which guaranteed human rights. The 1966 Constitution which contained entrenched Bill of Rights was suspended in 1970. From 1970 until 1993, Lesotho was governed undemocratically. There were no periodic elections as prescribed by the 1966 Constitution. The 1970 interim authority introduced orders which administered the country. Around that time, besides interim orders, the country was governed through military dictates, 90 days detention without trial and state of emergency laws and regulations. Citizens were arrested, searched and charged arbitrarily by the governments of the day. The study, firstly, commences with a thorough investigation of the violation of the fundamental human rights. It gives a historical background of Lesotho political landscape, legal system, Lesotho mounted police service evolution, and practical human rights violations. The study, secondly, draws a comparative scenario between Lesotho, the Republic of South Africa, the United States of America and the United Kingdom as far as human rights violations are concerned. The question of police use of force, whether deadly or moderate, while conducting arrest, search or seizure, has been thoroughly investigated and discussed. Human rights material, documents and instruments internationally or locally have been identified, analyzed and discussed. Based on the findings of the research, lessons and recommendations for Lesotho have been drawn. The study argues that generally speaking, there are no adequate control mechanisms put in place to regulate police powers in Lesotho compared to other jurisdictions. It further argues that, some jurisdictions, such as the United Kingdom, the Republic of South Africa and the United States of America have some advanced police intervention programmes aimed at improving and constantly checking police work. The Republic of South Africa in particular, has moved away from the apartheid past tendencies and legacy which saw the police use repressive means in dealing with the public unrest. For example, the principle of Parliamentary Sovereignty encouraged them to abuse their power as illustrated in the decision of Sachs v Minister of Justice' where the Judge had this to say: "Arguments are sometimes advanced which do seem to me to ignore the plain principle that Parliament may make any encroachment it chooses upon life, liberty and property of any individual subject to its sway, and that it is the function of the courts of law to enforce (Parliament's will)." However, this scenario changed with the introduction of the interim Constitution of 1993 which ushered in a democratic majority rule in 1994. The introduction of the 1993 interim Constitution brought with it a Constitutional State founded on the supremacy of the Constitution and the rule of law as opposed to a long practiced Parliamentary rule.

Sedert die wêreldwye instelling van die beginsel van basiese menseregte tree die kwessie van skending van menseregte in kriminele ondersoeke na vore as een van die mees bespreekte sake onder akademici. Menseregte bly die kern en spilpunt waarom die kriminele regstelsel wentel. In Lesotho byvoorbeeld, was die kwessie van menseregte van besondere belang in die lig van die feit dat daar sedert onafhanklikheidswording op 4 Oktober 1966, nooit 'n reële en tasbare instrument was wat menseregte gewaarborg het nie. The 1966 het die Grondwet die Handves van Menseregte verskans, maar dit is in 1970 opgehef. Van 1970 tot 1993 is Lesotho ondemokraties regeer. Daar was geen gereelde verkiesings soos deur die 1966 Grondwet voorgeskryf is nie. Die 1970 interim owerheid het maatreëls ingestel waarvolgens die land geadministreer is. Gedurende daardie tyd, benewens die interim reëlings, is die land deur militêre regulasies geregeer: 90 dae detensie sonder verhoor en volgens die wette en regulasies soos tydens 'n noodtoestand. Burgers is gearresteer, deursoek en arbitrêr aangekla deur die aktiewe regering. Die studie neem 'n aanvang met'n deeglike ondersoek na die skending van basiese menseregte. Dit verskaf geskiedkundige agtergrond van Lesotho se politieke omgewing, die regstelsel, die ontwikkeling van die Lesotho berede polisiemag en die aktiewe skending van menseregte. Die studie vergelyk vervolgens die voorkoms van die skending van menseregte in Lesotho, die Republiek van Suid-Afrika, die Verenigde State van Amerika en die Verenigde Koninkryk. Die vraag na die gebruik van geweld deur die polisie, hetsy of dit tot die dood lei of gematig is, by gebruik tydens arrestasies, deursoeking en inhegtenisnemings is deeglik ondersoek en bespreek. Bronne aangaande menseregte, insluitende dokumente en ander instrumente, internasionaal of plaaslik, is geïdentifiseer, geanaliseer en bespreek. Gegrond op hierdie gevolgtrekkings en bevindings wat die navorsing aan die lig gebring het, is aanbevelings vir Lesotho opgestel. Die studie kom tot die gevolgtrekking dat algemeen gesproke, daar in vergelyking met ander jurisdiksies, nie genoegsame beheermaatreëls in plek is om die polisie se magte te reguleer nie. Daar word verder aangevoer dat sommige jurisdiksies, soos die Verenigde Koninkryk, die Republiek van Suid-Afrika en die Verenigde State van Amerika gevorderde programme vir polisie-intervensie het wat op die verbetering en konstante monitering van polisiewerk, gemik is. Die Republiek van Suid-Afrika in besonder, het wegbeweeg van die apartheidsera waar die neiging was dat die polisie onderdrukkende metodes gebruik het in hulle hantering van openbare onluste. Die beginsel van Parlementêre Soewereiniteit byvoorbeeld, het hulle aangemoedig om hulle magte te misbruik, soos geïllustreer deur die besluit van Sachs v Minister of Justice" waar die Regter die volgende gesê het: "Arguments are sometimes advanced which do seem to me to ignore the plain principle that Parliament may make any encroachments it chooses upon life, liberty and property of any individual subject to its sway, and that it is the function of the courts of law to enforce ( Parliament's will)." Hierdie beginsel het egter verander met die instelling van die interim Grondwet van 1993 wat die voorloper was van die demokratiese meerderheidsregering in 1994. Die instelling van die 1993 interim Grondwet het 'n konstitusionele staat, gegrond op die oppergesag van die Grondwet en die regsorde teenoor die lank gebruikte parlementêre wetgewing, ten gevolg gehad.
Thesis (LL.D. (Procedural Law and Law of Evidence))--University of the Free State, 2010
Keywords: Criminal investigation -- Lesotho; Criminal investigation -- Case studies; Human rights-- Lesotho; Respect for persons -- Law and legislation -- Lesotho; Police misconduct -- Law and legislation -- Lesotho; Police -- Lesotho -- History